Selling repurposed furniture: An exploratory study into consumer perception - Sumter, Deborah Xaviera; Snäll, Bente; Oskam, Inge F. (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Repurpose is becoming more popular as a circularity strategy. This circularity strategy is specifically promising in the case of furniture. One of the challenges of upscaling repurpose is the negative consumer perception of repurposed products. Studies up to date pertain to consumer perception of refurbished products and products using recycled content. In this study we investigate (1) to which extent the motives mentioned within literature play a role when it comes to consumers’ perception of repurposed furniture and (2) to what extent the visibility of past identity of repurposed furniture and storytelling play a role in consumer perception. The result indicate that aesthetic and functional quality are highly valued. Storytelling seems to be a secondary motive for customers to consider a repurposed product. We further identified three categories of repurposed furniture (i.e., visibly repurposed, non-visibly repurposed and unique look) that appeal to different consumer segments. While further research can be done into the demographic profiles, these categories can be used by designers/makers to make repurposed products that better appeal to their envisioned customer base.